The Role of Altruism, Self-Compassion, and Self-Monitoring in Blood Donors: Peran Perilaku Altruisme, Self-Compassion, dan Self-Monitoring pada Pendonor Darah - Putri, Jala Senastri; Asiyah, Siti Nur (Universitas Brawijaya, 2024)
Donating blood is a very useful activity, and the reasons for donating blood are also varied, such as wanting to help others by donating their blood, having experience of family members needing blood but running out, and finding it difficult to find blood donors willing to donate blood, and social rewards. Based on this, the study aims to determine the effect of self-compassion and self-monitoring on altruistic behavior in early adulthood blood donors in Surabaya. The method used is quantitative correlation. Data collection used the altruism scale, self-compassion scale, and self-monitoring scale for 347 blood donors. Data analysis using multiple linear regression. The results of this study indicate that there is an influence between self-compassion and self-monitoring on altruism behavior in early adulthood blood donors. This research suggests that having high levels of self-compassion and self-monitoring is a prerequisite for engaging in altruistic behavior, such as giving blood to patients in need. Keywords: self-compassion, self-monitoring, altruism behavior, blood donors, early adult